The analysis process degradation of radio equipment - Соломенцев, О. В.; Заліський, М. Ю.; Герасименко, Т. С. (Problems of Informatization and Control, 2015)
The procedure of statistical data on parameter estimation processors degradation of radio equipment in appropriate systems of exploitation-ted. The analysis procedure proposed by analytical calculations and mathematical modeling of assessment